The story of Dinah: rape and rape myth in Jewish tradition - Ruit, Gavi S. (Lexington Books/Fortress Academic, 2019)
Introduction: looking for answers -- Rape in the Hebrew Bible: was Dinah raped? -- Intertestamental period: supportive beginnings -- Rabbinic period: the introduction of rape myth -- Medieval period: redeeming Dinah -- Modern period: Orthodox commentaries -- Modern period: progressive commentaries -- Modern midrash and rape myth: everything old is new again -- Conclusion: Jewish tradition and rape myth.